Viability analysis of using cellulose pulp recycled from cement sacks in the production of compressed earth blocks - Buson, M. (2012)
This study concerns the development and analysis of the Kraftterra composite – raw earth stabilized with disperse fibers made with kraft paper from recycled cement sacks – for the production of CEBs and mortar for masonry infill elements. Its main goal is to define the behavior of small walls (prisms) of Kraftterra in relation to diagonal compression. The tests show that the prisms produced with Kraftterra CEBs and mortar show excellent bond strength between block and mortar. All the prisms tested presented fissure lines very close to the normal load line and the fissures occurred in the blocks and in the mortar in similar manner, without separation between these elements. The mortar produced with Kraftterra results in strong bonds between blocks and produces homogeneous construction elements with uniform performance, that is, with high monolithicity.